A novel Wilkinson power divider using lowpass filter with harmonics suppression and high fractional bandwidth. (January 2018) - Karimi, Gholamreza; Menbari, Samira
Abstract: In this paper, a new compact Wilkinson power divider using lowpass filter is presented. The proposed structure suppresses from 2nd to 6th harmonics with an attenuation level less than −20 dB and reduces the occupied area to 43.5% in comparison to the conventional Wilkinson power divider. Also, it generates a wide stop-band bandwidth (5.1 GHz–16 GHz). In addition, fractional bandwidth is equal to 44%. According to the measured frequency responses, input and output return losses are more than 27 dB and isolation is better than 46 dB at a center frequency of 2.55 GHz.